Latke, the lucky dog - Fischer, Ellen, 1947-; Beeke, Tiphanie (Minneapolis : Kar-Ben Publishing, 2014)
"A family rescues a dog from a shelter during Hanukkah, and the pup proceeds to create holiday hijinks as he gets used to his new home"--
Keywords: Dogs -- Fiction; Hanukkah -- Fiction